Russian real wages before and after 1917: in global perspective - Allen, R; Khaustova, E (University of Oxford, 2017)
The paper measures real wages in St Petersburg, Moscow, and Kursk between 1853 and 1937 and compares them to real wages in Boston, Manchester, Bombay, and Cairo. Russian living standards grew little between 1853 and 1913 and were like Egypt and India. Wages in the UK and USA were 2.5 - 5 times greater. Real wages in Russia almost doubled between 1913 and 1928. When seen in a Russian perspective, this looks like a big advance; when seen internationally, it is much less so. Real wages dropped to their pre-War level between 1928 and 1937 during the industrialization drive.